Pengaruh Kepemilikan Managerial, Institutionalo Prrblik, dan f)kuran Ilewan Direksi Terhadap Nilai Penrsahaan dengan Return On Asset Sebagai Variabel Kontrol - Sonny Feriawan (Jurnal Riset Manajemen dan Bisnis, 2010)
This research is to see the influence of managerial, institutional, and public ownership and the size of top milMgernent on the value of companies with the return on assets as the controlling variable. This study nkes the benefi* of 67 samples of companies during the period of 2005-2007, which are listed in the Indonesia Stock Exchmrge (BED.By using double regression, it indicates that the managerial ownership and the size of top management have a positive inJluence on the value of the companies. The institutional ownership and the public ownership do not have any influences on thevalue of the companies.Keywords: tnanogerial, institutional, public, the size of top mantagernent, return on assets (ROA), thevalue of company.